Reactive Oxygen Species in Plant Interactions With Aphids - Goggin, Fiona L.; Fischer, Hillary D. (Frontiers in Plant Science, 2022)
Reactive oxygen species (ROS) such as hydrogen peroxide and superoxide are produced in plants in response to many biotic and abiotic stressors, and they can enhance stress adaptation in certain circumstances or mediate symptom development in others. The roles of ROS in plant-pathogen interactions have been extensively studied, but far less is known about their involvement in plant-insect interactions. A growing body of evidence, however, indicates that ROS accumulate in response to aphids, an economically damaging group of phloem-feeding insects. This review will cover the current state of knowledge about when, where, and how ROS accumulate in response to aphids, which salivary effectors modify ROS levels in plants, and how microbial associates influence ROS induction by aphids. We will also explore the potential adaptive significance of intra- and extracellular oxidative responses to aphid infestation in compatible and incompatible interactions and highlight knowledge gaps that deserve further exploration.